(untitled) (Herald of the National Children’s Medical Center, 2025)
Modern pediatric anesthesiology requires effective and safe techniques to minimize pain, reduce the need for opioids, and ensure a comfortable awakening. The use of multimodal analgesia, including magnesium sulfate (MGSO₄), is a promising approach to optimizing pain relief and muscle relaxation in children. MGSO₄ has a number of pharmacological effects that may be particularly useful in pediatric practice, including reducing pain sensitivity, enhancing the action of muscle relaxants, and stabilizing hemodynamics.